2016
DOI: 10.5194/esd-2016-1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonality and spatial variability of dynamic precipitation controls on the Tibetan Plateau

Abstract: Abstract. The Tibetan Plateau (TP) is the origin of many large Asian rivers, which provide moisture for large regions in South and East Asia. Therefore, the water cycle on the TP and adjacent high mountain ranges and especially the precipitation distribution plays an important role for the water availability for billions of people in the regions downstream of the TP. Based on the High Asia Refined analysis (HAR) we analyse the influence of dynamic factors on precipitation, enhancing or suppressing precipitatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…In winter (December–February), the AW source only appears in the water bodies to the west of the ETP, such as the eastern Mediterranean, the Red Sea, and the Persian Gulf, as well as partial land areas adjacent to the southwestern ETP, with most of AW contributions less than 2 mm (Figures m–o). The local recycling almost disappears in this season due to frozen ground and high wind speed over the ETP that inhibit the formation of convection systems (Curio & Scherer, ; Guo & Wang, ). AW input to the ETP in winter is only 3–7% of the annual totals (Figure ).…”
Section: Aw Source To the Etpmentioning
confidence: 99%
See 1 more Smart Citation
“…In winter (December–February), the AW source only appears in the water bodies to the west of the ETP, such as the eastern Mediterranean, the Red Sea, and the Persian Gulf, as well as partial land areas adjacent to the southwestern ETP, with most of AW contributions less than 2 mm (Figures m–o). The local recycling almost disappears in this season due to frozen ground and high wind speed over the ETP that inhibit the formation of convection systems (Curio & Scherer, ; Guo & Wang, ). AW input to the ETP in winter is only 3–7% of the annual totals (Figure ).…”
Section: Aw Source To the Etpmentioning
confidence: 99%
“…Generally, AW transport to the ETP is dominated by the seasonal interaction between the westerlies and the Indian monsoon (Joswiak et al, ; Yao et al, , ), and the change of hydrological states over the TP is highly consistent with the interannual variability of large‐scale circulation systems (Curio & Scherer, ; Jiang & Ting, ; Li & Garzione, ; Mölg et al, ). For example, Gao et al () revealed that the humid southeastern TP was getting drier while the vast arid and semiarid northwest was getting wetter in 1979–2011; this was attributed to the poleward shift of the westerly jet and the intensification of Indian monsoon.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the precipitation in WRF control case and GPM differs in the amount but generally consistent in the spatial pattern with respect to the dry‐belt detected region. Besides, other studies also support the finding that WRF is capable of depicting the spatial pattern of precipitation over the TP (Maussion et al, ; Curio & Scherer, ; Ma et al, ; Collier & Immerzeel, ; Bookhagen & Burbank, , Bookhagen & Burbank, ).…”
Section: Resultsmentioning
confidence: 63%
“…There has been many studies in the water vapor transport (WVT) and precipitation over the TP. For example, Curio and Scherer () indicated that the WVT from outside the region can contribute to about 40% precipitation over the TP. Bookhagen and Burbank (, ) showed that the high terrain is a barrier that rarely permits the water vapor to enter the TP and only the valleys over HMs are the primary vapor channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation